PERANAN ARANG BATANG KELAPA SAWIT DALAM PENINGKATAN PRODUKSI TANAMAN JAGUNG (ZEA MAYS, L.) - Febrianti - (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
The main problem of continuously cultivatedland is decreasing land productivity. Improvement of land productivity can be done by application ofsuitable soil ameliorant. Charcoal is one of soil ameliorants that can be used for improving soil properties such as to stimulate plant growth by providing and maintaining nutrients in the soil due to improving soil physical and biological properties. Abundant availability of oil palm trunks when oil palm replanting is an opportunity to utilizeoil palm trunks as charcoal raw material. This research aimed to study the effect of charcoal from oil palm trunks on corn growth and production.Soil material was taken from Latosol at a depth of 0-20 cm. The soil material was treated by charcoal from oil palm trunks as much as 0%, 4%, 8%, 12%, 16% and 20% (w/w) of the soil.The soilalso was addded by basic N, P, and K fertilizers and then corn was planted. The results showed that soil treated by 4%ofcharcoal fromoil palm trunks increasedsignificantly corn growth and production. Application of higher charcoal rates did not increasethe growth and production of corn, and moreover tended to decrease at20% charcoal treatment. Biomassproduction of cornincreased significantlycompared tountreatedcharcoal.The porous structure of charcoal improve the structure of soils which allows rootscapable to utilizemore available nutrients as indicated bythe evidence of moreroots inthesoil containingcharcoal and increasing corn production. Key words :charcoal., oil palm trunks., corn production., soil ameliorant